2005
DOI: 10.1007/s11010-005-4504-z
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effects of hypoxia-mimicking divalent cobalt ions in human endothelial cells in vitro

Abstract: Divalent cobalt ions (Co2+) induce the expression of hypoxia responsive genes and are often used in cell biology to mimic hypoxia. In this in vitro study we compared the effects of hypoxia and Co2+ on human endothelial cells and examined processes that are stimulated in hypoxia in vivo (proliferation and angiogenesis). We analyzed the expression of the hypoxia-inducible factor-1alpha (HIF-1alpha) under different hypoxic conditions (3% and nearly 0% O2) and Co2+ -concentrations (0.01-0.7 mM). As in hypoxia, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 47 publications
2
48
1
3
Order By: Relevance
“…In contrast to DPSC, no differences were seen after exposure of SHED to the 1Co BG or to the 0Co BG or CTL conditions. This suggested that cobalt ions may trigger different responses depending of the source of dental stem cells, as previously demonstrated in other cell types such as periodontal cells [17], endothelial cells [11], and bone marrow stem cells [16]. While cobalt-containing BG have the potential to stimulate the release of angiogenic growth factors in DPSC, and may benefit dental repair when associated with such cell types, further investigations would be needed to better understand how different dental progenitor cell types are influenced by cobalt.…”
Section: Dental Stem Cells Secrete Increased Level Of Vegf In Responssupporting
confidence: 56%
See 2 more Smart Citations
“…In contrast to DPSC, no differences were seen after exposure of SHED to the 1Co BG or to the 0Co BG or CTL conditions. This suggested that cobalt ions may trigger different responses depending of the source of dental stem cells, as previously demonstrated in other cell types such as periodontal cells [17], endothelial cells [11], and bone marrow stem cells [16]. While cobalt-containing BG have the potential to stimulate the release of angiogenic growth factors in DPSC, and may benefit dental repair when associated with such cell types, further investigations would be needed to better understand how different dental progenitor cell types are influenced by cobalt.…”
Section: Dental Stem Cells Secrete Increased Level Of Vegf In Responssupporting
confidence: 56%
“…This concentration appeared suitable to induce cobaltdependent cellular responses, e.g. HIF-1 pathway activation and VEGF expression [11]. …”
Section: Incubation Of Cobalt-containing Bg Into Cell Culture Medium mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when coupling different solicitations (as wear or fretting and corrosion), the protective passive layer of chromium oxide is no more sufficient to protect it from catastrophic wear and release of metallic (nano-) particles in the body [3]. They may then act as wear third body, leading to a more pronounced degradation of the metallic prosthesis or its UHMWPE counterpart, or poison the human body fluid, leading to various cell necrosis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…27 1393 bioactive glasses tolerate strong bonding to hard and soft tissue and have been shown to endorse osteogenesis via the activation of several relevant genes. 28 Cobalt ions are considered important in bone physiology [29][30][31][32] as they induce hypoxia conditions and become stable hypoxia-inducible factor 33,34 which in turn, activates several pro-regenerative processes in the human body. 35 HIF-1 activation leads to angiogenesis, stem cell differentiation, and fracture repair.…”
Section: Introductionmentioning
confidence: 99%